FACTORS INFLUENCING THE STUDENTS TO JOIN IN INCUBATION CENTERS OF ACADEMIC INSTITUTIONS IN BANGALORE CITY, KARNATAKA STATE - N, NAGENDRA PRASAD; GANESAMOORTHY, Dr.L. (South Eastern European Journal of Public Health, 2024)
The primary motive of this research paper is to study the level of influence of motivational factors on the students to join in incubation centres functioning in colleges in Bangalore city. The researcher considered 689 students who were studying commerce and management courses from 86 colleges, from whom the primary data were gathered through questionnairein online mode. The researcher identified a total of 23 factors which probably influence them. The researcher applied Factor Analysis, Descriptive Statistics (Mean, Standard Deviation and Co-efficient of variation), t-test and One-way ANOVA for analysing the data. The study found that the “Factors Related to Favourable Business Conditions” influenced the respondents more to join in incubation centres followed by the factors “Psychological Factors”, “Academic and Incubation Centre Related Factors” and “Financial and Employment Related Factors” and the factor “Family and Personal Factors” influenced to a moderate extent on the respondents to join in incubation centres. The study also evidenced that significant differences were found in level of influence of family and personal factors with the factors native area, family size, parent’s occupation and income. There were significant differences in level of influence of financial and employment related factors with the factors native area, family size, parent’s occupation and income. Significant differences was there in Factors of Favourable Business Conditions with native area, parent’s occupation and type of institution. Type of institutions made significant differences in Academic and Incubation Centre Related Factors.